2019
DOI: 10.1002/elan.201800710
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Paste Composite with Co3O4 as a New Electrochemical Sensor for the Detection of Allura Red by Reduction

Abstract: The detection of Allura red (AR) by electrochemical reduction using a different electrode from the conventional mercury electrode is presented. A carbon paste with cobalt (II, III) oxide composite electrode (CoOx/CPE) is reported for the first time for the detection of AR. Moreover, others dyes such as tartrazine (TZ), sunset yellow (SY), amaranth (AM), Ponceaut 4‐R (P‐4R), and Sudan (SD) as well as pharmaceutical agents such as paracetamol (PMC) that are present in samples that contained AR did not show a red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 39 publications
3
21
0
Order By: Relevance
“…These results indicate that the charge transfer rate was faster, due to the presence of metallic complex in the electrode. Similar results have been reported for CPE decorated with other metal ions, such as Co and La, where the presence of the metal ions did not change the potential value considerably, but the anodic and cathodic peak currents were increased [28,29]. The EDS image of the Cu C /CPE microstructure (Figure 1C) shows the presence of C as well as N, Cu and Cl.…”
Section: Electrochemical Properties Of the Carbon Paste Surface Decorsupporting
confidence: 86%
“…These results indicate that the charge transfer rate was faster, due to the presence of metallic complex in the electrode. Similar results have been reported for CPE decorated with other metal ions, such as Co and La, where the presence of the metal ions did not change the potential value considerably, but the anodic and cathodic peak currents were increased [28,29]. The EDS image of the Cu C /CPE microstructure (Figure 1C) shows the presence of C as well as N, Cu and Cl.…”
Section: Electrochemical Properties Of the Carbon Paste Surface Decorsupporting
confidence: 86%
“…Recently, reports of electrodes modified with metal oxides have increased. Some reports of modified electrodes used cobalt oxide for detecting H 2 O 2 , As(III) and allura red [1][2][3], ruthenium oxide for detecting carbohydrates [4], nickel oxide for detecting glucose [5], zinc oxide for detecting hydrazine [6,7], neodymium oxide for detecting dopamine, sunset yellow and tartrazine [8,9] and lanthanide oxide for detecting thiomersal [10]. In these reports, several characteristics are observed that confirm the electroactive properties of these substances with the modified electrodes.…”
Section: Introductionmentioning
confidence: 79%
“…On the other hand, some of the most notable advantages of MoO 2 and other metals oxides, that justify the use in the modification of electrodes are; low toxicity, high chemical and thermal stability and a high dielectric constant [24]. Moreover, the currents increase considerably, possibly, electrostatic interactions between the metal ion and the analyte occur with an increase in the surface area [14,25]. Therefore, there is evidence of the great activity of metal ion oxides in the preparation of low-cost electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…To address the above-mentioned issues, much effort has been made to develop novel modified electrodes that are capable of efficiently detecting Allura Red based on the oxidation signals. Novel electrochemical sensors based on multiwalled carbon nanotube (MWCNT) [28,29], ionic liquids [30], cobalt oxide [31], and cobalt complex [32] modified electrodes have shown great potentials on the detection of Allura Red, due to their excellent accumulation efficiency and large specific surface area. For example, MWCNT/GCE showed a wide linear response range of 496-4468 µg/L, and it was applied to the analysis of commercial isotonic sports drinks with satisfactory results [28].…”
Section: Introductionmentioning
confidence: 99%